Predictive Ability, Marketing Prices, and Operating Flows. - Revsine, Lawrence (The Accounting Review, 1971)
The article focuses on predictive ability, market prices, and operating flows. One normative function of external accounting reports is to provide information which will be useful to decision makers in generating estimates of the future levels of relevant variables. The reporting objective which follows from this belief is commonly called the predictive ability criterion. Predictive ability claims have been advanced in the past as support for the adoption of replacement cost income measurements. As knowledge of users' decision models is limited, the basic issue of precisely what the appropriate object of prediction should be has received little explicit attention. In the case of the current operating profit component of replacement cost income, there has been general acceptance for the a priori notion that this concept aids in the prediction of future operating income. Since income from operations and holding gains or losses result from different causes, they can be expected to have different patterns of recurrence. Effective prediction of future income is facilitated by reporting them separately.